Pd, Au and codeposited Pd-Au ultrathin films on Ru(001) - Fauster, Thomas; et al. (Surface Science, 1997)
The growth of ultrathin Pd, An and codeposited Pd/Au films on Ru(001) at 470 K is studied by low-energy ion scattering. Both Pd and Au grow as flat two-dimensional layers up to two monolayers. The first layer of the codeposited films also grows (nearly) as a two-dimensional monolayer, independent of the deposition sequence. The data are most easily explained assuming only little (or no) Pd-Au alloying. (C) 1997 Elsevier Science B.V.
Keywords: epitaxy; gold; low energy ion scattering; low index single crystal surfaces; palladium; ruthenium; surface structure; morphology; roughness; and topography